Using Authenticity Event as a Factor that Affects Event Attendance in Improving Branjang Tourism Village Promotion - Pranoto, Pranoto; Listyorini, Haniek; Mistriani, Nina (Journal of World Science, 2022)
Introduction: During the Covid-19 pandemic, many tourist villages are reluctant to develop their respective destinations. The manager of the Branjang Tourism Village, Semarang Regency, realized the importance of events in destination development by exploring the impact of event attendance on destination promotion. This study first aims to analyze the effect of the authenticity of the event on the attendance of the event. The second explores the impact of event attendance on destination promotion. The third examines the direct impact of actual authenticity on destination promotion. Fourth, prove the mediation of event attendance in the effect of event authenticity on destination promotion. Methods: To test this model, 100 respondents of tourists who visited the event were taken at the Branjangan Cultural Event in the Branjang Tourism Village. Then the data is processed using SEM PLS. Result: The authenticity of the event influences the attendance of the event with t statistic 7,488> 1,96. Authenticity Events influence destination promotion with a t-statistic value of 4.011 > 1.96. The presence of the event influences destination promotion with a statistical t value of 3.507> 1.96 and the authenticity of the event on destination promotion influences the presence of the event with a simultaneous value of 0.2880> 1.96. Conclusion: The results of the first study show that the authenticity of the event affects the attendance of the event; second, the presence of the event affects the promotion of the goal. Thirdly, event authenticity involves the promotion of goals, and event attendance mediates the effect of event authenticity on goal promotion.